Galerkin approximations for the Dirichlet problem with the -Laplacian. (January 2019) - Pastukhova, S. E.; Yakubovich, D. A.
Abstract: We study the Dirichlet problem with -Laplacian in a bounded domain, where is a measurable function whose range is bounded away from and . A system of Galerkin approximations is constructed for the so-called -solution or any other variational solution, and energy norm error estimates are proved. References: 19 items.